ANALISIS PENGARUH RELIGIUSITAS, KELOMPOK REFERENSI DAN MOTIVASI TERHADAP KEPUTUSAN MENABUNG DI BANK SYARIAH (Studi Pada Nasabah Bank Syariah di Kota Banjarmasin) - Wahyu Utami; Marijati Sangen; M. Yudi Rachman (JWM (JURNAL WAWASAN MANAJEMEN), 2015)
This study has the objective to determine the effect of religiosity, reference groups and the motivation factors to the decision to save in Islamic banks. Location of the research conducted in the city, Banjarmasin. With population all of Banjarmasin’s Islamic bank individual customers, using purposive sampling methods with 100 numbers of respondents in finishing the survey. Results of hypothesis testing with multiple linear regressionat the 95% confidence level, indicates that religiosity, reference groups, and the motivation factors, either partially or simultaneously influence the decision to saving in Islamic banks. Partially, religiosity factor is the most dominant factor in influencing people to take decisions to saving in Islamic banks. Therefore, to increasing the amount of savings customers, Islamic banks should go through a religious approach. Increased socialization of the importance of Sharia principles in everyday life, products and excellence of Islamic banks need to be done through religious activities such as teaching, tadarus, boarding lightning, lectures at Friday prayers and Taraweeh, and other religious activities.